Landowner Willingness to Accept Monetary Compensation for Managing Forests for Ecosystem Services in the Southern United States - Ram K Adhikari; Robert K Grala; Daniel R Petrolia; Stephen C Grado; Donald L Grebner; Anusha Shrestha (Forest Science, 2022)
Distributional specifications of the willingness-to-accept function affect the accuracy of welfare estimates when the contingent valuation model includes unsure responses. By exponentiating the bid variable, we implemented an improved methodological approach to estimate four discrete choice models reflecting treatment of unsure responses. Landowners required an average compensation of $93 acre−1 year−1 to participate in a 10-year conservation program. The probability of participation was positively influenced by payment amount, concern about wildlife habitat loss, contact frequency with the Natural Resources Conservation Service, and education level. Findings will help determine regional-level budgets for various conservation scenarios facilitating an increased production of ecosystem services. Study Implications Conservation agencies can decrease landowner uncertainty that arises from limited information about conservation programs and motivate landowners to enroll in a conservation program facilitating an increased production of ecosystem services by offering adequate monetary incentives. Conservation agencies can provide similar financial compensation for conservation of bottomland hardwoods and pine stands but will most likely need to offer greater compensation for the protection of forests prone from impacts by wildfires, hurricanes, and tornadoes. Available funding should be prioritized for conservation of critical habitats and freshwater sources vulnerable to land disturbances.